2008
DOI: 10.1007/s11094-009-0204-4
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the lipophilic fraction of stinging nettle (Urtica dioica L. and U. urens L.) homeopathic matrix tinctures

Abstract: The composition of lipophilic fractions of homeopathic matrix tinctures of Urtica dioica L. (I) and U. urens L. (II) derived from freshly collected plants and dried (desiccated) material (herb and roots) was studid using GC-MS techniques. The analyses of n-hexane extracts of tincture I revealed 43 compounds (of which 27 were identified) whereas the analysis of the extract of tincture II revealed 28 compounds (21 identified). The extract from I contains fatty acids in the form of ethyl esters, terpenoids (apiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The phytochemical composition investigation on U. dioica [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28] revealed that it contains phenolic compounds (including flavonoids, tannins, coumarins and lignans), sterols, fatty acids, polysaccharides and isolectins.…”
Section: Phytochemical Investigations and Biological Activities Ofmentioning
confidence: 99%
“…The phytochemical composition investigation on U. dioica [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28] revealed that it contains phenolic compounds (including flavonoids, tannins, coumarins and lignans), sterols, fatty acids, polysaccharides and isolectins.…”
Section: Phytochemical Investigations and Biological Activities Ofmentioning
confidence: 99%
“…Taxonomy of U. dioica for ethnobotanical, especially complementary and alternative medicinal usages might have some complications due to wide range of habitats, and the heterogeneity of the morphological traits such as phenolic contents and antioxidant capacities of plants. Different parts of the U. dioica contain completely different chemicals which can be extracted in different ways such as the root of the U. dioca contains polysaccharides which are believed to be responsible for its anti-inflammatory effects and unidentified components present in certain aqueous, but not lipophilic extracts and/or similar chemicals with different concentrations in different parts of the same plant (Lapinskaya et al, 2008a(Lapinskaya et al, , 2008b. To overcome various complications and difficulties in diagnosis of this species and to get rid of the need for personal expertise and experiences we designed a set of species specific primers for the U. dioica agglutinin isolectin VII precursor (chia5.7.2) gene, exon 3 (UDA) which encodes UDA protein that is a single-chain peptide found in roots and rhizome of U. dioica (Van Damme and Peumans, 1987) and used it for both molecular diagnostics and further to assess genetic variation using real-time PCR and HRM analysis in combination with universal, conserved chloroplast DNA sequence 16S rRNA gene (5' Brown, 2002).…”
Section: Introductıonmentioning
confidence: 99%